Impact of Drip Irrigation and Nitrogen Fertilization on Soil Microbial Diversity of Spring Maize - Sarula; Hengshan Yang; Ruifu Zhang; Yuanyuan Li; Fanhao Meng; Jinhui Ma (Plants, 2022)
Given the shortage of water resources and excessive application of nitrogen fertilizers in irrigated areas, we explored the effect of water–nitrogen coupling on soil microbial diversity in maize fields irrigated using shallow buried droppers. A field experiment (split-plot design) was used with irrigation amounts set at 40%, 50%, and 60% of the conventional amount; furthermore, 13 water and nitrogen coupling treatments were designed. The secondary area was the nitrogen application level, corresponding to 50%, 70%, and the original conventional application amounts. The results showed that the effect of irrigation amount on bacterial community composition was greater than that of nitrogen, whereas the effect of nitrogen on fungi was greater than that on bacteria. No significant difference was detected in the α diversity index or species richness of bacteria and fungi. Available phosphorus and organic carbon contents significantly correlated with the community structure of soil bacteria (p < 0.05). The relative abundances of bacteria and fungi were stable with the decrease of nitrogen application rate at the irrigation rate of 2000 m3 ha−1. With the decrease of irrigation amount, the relative abundance of bacteria and fungi was stable under the treatment of 210 kg ha−1 nitrogen fertilizer. Moreover, the relative abundance of nitrogen-fixing bacteria related to the nitrogen cycle was increased by irrigation of 2000 m3 ha−1 and nitrogen application of 210 kg ha−1. Moderate reduction of subsequent N supply should be as a prior soil management option in a high N input agroecosystem.